SCIENTOMETRIC DIMENSIONS OF TECHNICAL REPORTS FROM BHABHA ATOMIC RESEARCH CENTRE - T., Swarna; V.L., Kalyane; Vijai, Kumar (Malaysian Journal of Library and Information Science, 2002)
Technical report is one of the media to record the scientific information generated by scientists and engineers. Bhabha Atomic Research Centre (BARC) published 554 technical reports during 1990-99 under the categories: External (373) and Internal (181). Engineering and technology generated 207 technical reports followed by chemistry, materials and earth sciences (129), while their interdisciplinary interactions resulted in 31 technical reports. Life and environmental sciences produced 42 technical reports; followed by Physics (16); Other aspects of nuclear and non-nuclear energy (6); Isotopes, isotope and radiation applications (4). Technical reports in subjects outside the scope of nuclear science and technology were 69. Scientometric analysis of these reports has been carried out for physical bibliographic characteristics, authorship collaboration, inter-divisional collaboration, inter-institutional collaboration activities and content analysis. Types of documents referenced in the technical reports indicated first rank for journal articles, followed by books, technical reports, conference papers, standards/codes, personal communications, patents, theses, drawings, and lectures.